Unit Cost Analysis of Central Sterile Supply Department (CSSD) using Activity Based Costing Method in PKU Muhammadiyah Bantul Hospital - Firman Pribadi; Avi Syifa; Mariska Urhmila (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
PKU Muhammadiyah Bantul Hospital has not set sterilization rates in the Central Sterile Supply Department (CSSD) unit since 2017. The calculation of unit cost using the activity-based costing (ABC) method. The method aimed to obtain information on budget planning, cost control, and pricing by developing estimated costs by dividing an action into activities that can be divide based on units of work. The unit cost calculation process is expected to improve the efficiency and performance of each installation and polyclinic. Also, all service process components at health service providers can be well monitored. This research used a descriptive qualitative with a case study approach. This study aims to analyze the unit cost of sterilization in the CSSD unit based on the Activity-Based Costing (ABC) method. Based on the results, the unit cost of sterilizing the CSDD unit at PKU Muhammadiyah Bantul Hospital using the Activity Based Costing method was Rp. 2,049,388.00. The total unit cost of one sterilization procedure on average in CSSD units.